Interval Training and Endurance Training to Increase VO2max: Article Review - Fajar Syamsudin; Rony Syaifullah; Muhammad Bakhtiar Subardi; Sayid Fariz (STKIP Muhammadiyah Kuningan, 2021)
This study aims to determine better between Interval Training and Endurance Training to increase VO2max capacity in healthy adult men and women. The method used is a literature review, looking for articles from Electronic DataBased in PubMed, ScienceDirect, Eric. Journal, Google Scholar, and ProQuest that have been published and accredited. A total of 8 papers were selected for in-depth review. The results show that Interval Training is better than Endurance Training, even though both can increase VO2max.